2022
DOI: 10.1021/acsomega.2c04684
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Rheology and Stability of Heavy Crude Oil-in-Water Emulsions Using APG08 Emulsifiers

Abstract: This work investigates the performance of isooctyl glucoside (APG08) as an emulsifier for the preparation of a Karamay heavy crude oil-in-water emulsion to facilitate its pipeline transportation. First, various factors affecting the rheology and stability of prepared emulsions were studied. The results revealed that the viscosity and stability of emulsions increased with increasing oil content, surfactant concentration, mixing speed, mixing time, and pH of the aqueous phase. Emulsion viscosity was initially un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Indeed, it has been found that an increase in oil concentration decreases the creaming rate of emulsions due to an increase in emulsion viscosity and packed density of droplets as well as enhancement of interdroplet interactions [45]. Dong et al also showed that an increase in oil content produces a greater interfacial area between the oil and aqueous phase, resulting in a higher number of emulsified oil droplets with smaller size, thus increasing emulsion stability [46]. The rate of the creaming observed in emulsions F2 and F3 can be commented on based on Stokes' law (Equation ( 2))…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it has been found that an increase in oil concentration decreases the creaming rate of emulsions due to an increase in emulsion viscosity and packed density of droplets as well as enhancement of interdroplet interactions [45]. Dong et al also showed that an increase in oil content produces a greater interfacial area between the oil and aqueous phase, resulting in a higher number of emulsified oil droplets with smaller size, thus increasing emulsion stability [46]. The rate of the creaming observed in emulsions F2 and F3 can be commented on based on Stokes' law (Equation ( 2))…”
Section: Resultsmentioning
confidence: 99%